THE ROLE OF LINGUISTIC MOTIVATION IN FOREIGN LANGUAGE LEARNING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Motivation is widely recognized as one of the most influential factors in foreign language acquisition. Among various types of motivation, linguistic motivation occupies a special place, as it reflects learners’ intrinsic interest in the language system and its cultural context. This article examines the role of linguistic motivation in foreign language learning and analyzes its impact on learners’ engagement, autonomy, and academic achievement. Using a qualitative research approach based on theoretical analysis and review of existing studies, the research highlights the significance of linguistic motivation in fostering effective and sustainable language learning. The findings suggest that developing linguistic motivation should be a priority in modern foreign language education.